Grundtvig-Konference i Indien - Bugge, Knud Eyvin (Grundtvig-studier, 2000)
A Grundtvig-Conference in India By K.E. Bugge In January 1999 an international Grundtvig-conference was held in India. The venue was Jadavpur University, Calcutta. Since time immemorial Calcutta has been a seat of learning.Not only the classical religious texts were studied, but for more than 200 years the intellectuals of Calcutta have also been deeply involved in social and political issues. In the middle of the 19th century this blend of culture, scholarship and social reforms inspired a series of initiatives aiming at providing improved educational opportunities for the backward sections of society. The educational efforts of Jadavpur University (established 1956) must be understood in this perspective.